Significant Association Between CAV1 Variant rs3807989 on 7p31 and Atrial Fibrillation in a Chinese Han Population. Issue 5 (7th May 2015) - Chen, Shanshan; Wang, Chuchu; Wang, Xiaojing; Xu, Chengqi; Wu, Manman; Wang, Pengxia; Tu, Xin; Wang, Qing K.
Abstract : Background: Recent genome‐wide association studies (GWAS) in European ancestry populations revealed several genomic loci for atrial fibrillation (AF). We previously replicated the 4q25 locus ( PITX2 ) and 16q22 locus ( ZFHX3 ) in the Chinese population, but not the KCNN3 locus on 1q21. With single‐nucleotide polymorphism rs3807989 in CAV1 encoding caveolin‐1, however, controversial results were reported in 2 Chinese replication studies. Methods and Results: Six remaining AF genetic loci from GWAS, including rs3807989/ CAV1, rs593479/ PRRX1, rs6479562/ C9orf3, rs10824026/ SYNPO2L, rs1152591/ SYNE2, and rs7164883/ HCN4, were analyzed in a Chinese Han population with 941 cases and 562 controls. Only rs3807989 showed significant association with AF ( P adj =4.77×10 −5 ), and the finding was replicated in 2 other independent populations with 709 cases and 2175 controls, 463 cases and 644 controls, and the combined population with a total of 2113 cases and 3381 controls ( P adj =2.20×10 −9 ; odds ratio [OR]=1.34 for major allele G). Meta‐analysis, together with data from previous reports in Chinese and Japanese populations, also showed a significant association between rs3807989 and AF ( P =3.40×10 −4 ; OR=1.24 for allele G). We also found that rs3807989 showed a significant association with lone AF in 3 independent populations and in the combined population ( P adj =3.85×10 −8 ; OR=1.43 for major allele G). Conclusions: The data in this study revealed a significant association between rs3807989 and AF in the Chinese Han population. Together with the findings that caveolin‐1 interacts with potassium channels Kir2.1, KCNH2, and HCN4 and sodium channels Nav1.5 and Nav1.8, CAV1 becomes a strong candidate susceptibility gene for AF across different ethnic populations. This study is the first to show a significant association between rs3807989 and lone AF.